THE DEVELOPMENT OF ELECTRONIC BOOK ON "NUTRITION FOR ATHLETE" FOR THE CHONBURI PROVINCE ATHLETES IN SPORTS HERO PROJECT - Pipatmongkonchai, Chanaradee; Kormanee, Sukamit; Hoksuwan, Pongprasert (Academic Journal of Thailand National Sports University, 2019)
The purpose of this research was to develop electronic book on “nutrition for athlete” for chonburi province athlete in sports hero project have the 90 / 90 standard and comparison of test scores before and after learn with electronic book on “nutrition for athlete” for chonburi province athlete in sports hero project. The sample consisted of 31 athletes in sports hero project by cluster sampling. The research instruments included a electronic book on “nutrition for athlete” and practical test of nutrition for athlete. The results indicated that the efficiency of electronic book on “nutrition for athlete” for Chonburi province athlete in sports hero project have the 90/90 standard were 95.16/ 90.32 according to the criteria set and comparison of test scores before and after learn with electronic book on “nutrition for athlete” for Chonburi province athlete in sports hero project shown that after learn with electronic book the posttest results were higher than that pretest in the significance level of .05 according to the hypothesis.